Dominica : Staff Report for the 2005 Article IV Consultation, Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance of Performance Criterion, Financing Assurances Review, and Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Dominica is recovering from the aftermath of an economic and financial crisis in 2001-02 when output contracted by 10 percent. The reform strategy has been successful. Economic growth has recovered to more than 3 percent a year and is set to record the second straight year of above average growth in 2005. Inflation declined in 2004 and remains subdued in 2005 despite the higher energy prices. Reflecting strong fiscal consolidation and a collaborative debt restructuring agreement, public finances are now on a firmer footing.